As the 'Albino' takes on the fashion world - Moiloa, Bandile (The IIE, 2016)
This study is a completely explorative investigation that revolves around how Shaun Ross who is a male model with albinism has been represented in both Vogue and Zink Magazine, and to further gain an understanding into people’s perceptions surrounding persons with albinism and whether these perceptions have influenced they way in which they perceive persons with albinism in fashion photography as opposed to when encountering them in everyday society.
Thesis
Keywords: Alibinism; Fashion photography; Shaun Ross; Fashion magazine